2020
DOI: 10.17576/jkmjc-2020-3604-13
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Effect of Work Category on the Relationship between Professional Competencies` and Decision Making among Public Relations in Government- Linked Companies

Abstract: Organisational success can only be materialized when each stakeholder mutually agrees to benefit each other, thus making the organisation effective. And here is the main role of public relations (PR), were to be the middle person between each stakeholder, by performing their works through the competencies they mastered, to ensure that the decisions made will be valuable to organisation and stakeholders. The objective of this study is to examine the mediating effect of work category on the relationship between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
(14 reference statements)
1
1
0
Order By: Relevance
“…The findings further show that the perception of waqf towards Nadzir's professionalism has a significant positive effect on the intention of waqf at Pondok Modern Darussalam Gontor. This finding is in line with research conducted by (Basri & Maryanti, 2020;Johari et al, 2014;Samsudin et al, 2020). Furthermore, these findings can be generalized to waqf institutions in Indonesia, where the management of waqf must be trustworthy, transparent, and professional in order to continue to increase the waqf assets that are managed through the community's intention to do waqf.…”
Section: Hypothesis Testsupporting
confidence: 89%
See 1 more Smart Citation
“…The findings further show that the perception of waqf towards Nadzir's professionalism has a significant positive effect on the intention of waqf at Pondok Modern Darussalam Gontor. This finding is in line with research conducted by (Basri & Maryanti, 2020;Johari et al, 2014;Samsudin et al, 2020). Furthermore, these findings can be generalized to waqf institutions in Indonesia, where the management of waqf must be trustworthy, transparent, and professional in order to continue to increase the waqf assets that are managed through the community's intention to do waqf.…”
Section: Hypothesis Testsupporting
confidence: 89%
“…Studie's (Valeau, Paille, Dubrulle, & Guenin, 2021) stated that professionals have a significant positive effect on organizational commitment. (Samsudin, Abdullah, & Osman, 2020) found that professionalism has a positive and significant effect on decision making. From this previous research hypothesized that: H5 = Waqif's perception on nadzir's professional has positive signifigant affect on intention to act waqf.…”
Section: Trustmentioning
confidence: 99%